Desarrollo de las tablas de estado de equipos y gráficas de función secuencial en una interfaz gráfica de usuario (GUI) para las unidades de secado y extracción multipropósito en el Centro de Procesos e Innovación para la Industria Sostenible (CEPIIS) de la Universidad de América. (2024)
This project is proposed in order to develop equipment status tables and sequential function graphs in a graphical user interface (GUI) for the multipurpose drying and extraction units of the Purification and Refining Center (CEPURE) of the Center for Processes for the Sustainable Industry (CEPIIS) of the Universidad de América Foundation, is a project where a recognition of the instrumentation and control was carried out.